ANALISIS PENERAPAN PEMBELAJARAN BERDIFERENSIASI DALAM KURIKULUM MERDEKA DI SMAN 7 PADANG - Sri Hikmah Putri, Abna Hidayati; Rayendra, Mutiara Felicita Amsal (STKIP Subang, 2025)
The study aims to analyze the application of differentiated learning consisting of content differentiation, process differentiation, product differentiation, and learning environment differentiation carried out at SMAN 7 Padang. The method used is Mixed Method with the Concurrent Embedded Strategy model. This model uses quantitative methods and qualitative methods. In this model, there are those who act as quantitative data, namely subject teachers of grade XI phase F of SMAN 7 Padang and students of phase F with a sample size of 15 teachers and 56 students and qualitative data using the Miles and Huberman Model. The results of the study showed that the application of differentiated learning carried out at SMAN 7 Padang on content differentiation was in the